Spectrum of primary bone grafting in cranio maxillofacial trauma at a tertiary care centre in India - Arun Kumar Singh; Devi Prasad Mohapatra; Vijay Kumar (Indian Journal of Plastic Surgery)
Background: In past several years, traumas following road traffic accidents and other causes have increased, owing to an increase in mechanization and pace of life. These patients frequently have complicated injuries involving soft tissue and the craniofacial skeleton. Assessment of bony injuries and loss of portions of facial skeleton and their management has proved to be a challenge to the reconstructive surgeon. Aims: Primary bone grafting of craniofacial skeletal injuries provides an opportunity for one stage correction of bony defects. The varied spectrum of primary bone grafts for management of craniomaxillofacial injuries are evaluated in this study. Materials and Methods: Patients with a history of acute trauma resulting in facial skeletal injuries with or without bone loss were included in the study. Primary bone grafting was undertaken in situations requiring contour correction, replacement of skeletal losses and for rigid fixation of fracture segments. Olecranon, Iliac crest, ribs, Vascularized as well as nonvascularized outer table calvarial grafts and nonvascularized inner table calvarial grafts were used in this study. Results: Sixty two patients of craniomaxillofacial injury following trauma requiring primary bone grafting were considered in this study. Fifty seven percent of patients (n=32) required primary bone grafting for replacement of bone loss while bone grafting for contour correction was done in twenty three patients. The parietal calvaria overlying the non-dominant hemisphere was used as a source of bone graft in forty-nine patients. Nearly ninety-two percent of the patients were satisfied with the results of primary bone grafting. Conclusions: Functional and aesthetic assessment of each of these patients, managed with primary bone grafting revealed a low rate of disabilities and high percentage of satisfaction in this study.